Alzheimer's Disease in Individuals with Down Syndrome - Amadea, Muhammad Ikhsan (HM Publisher, 2023)
Down syndrome (DS) is a genetic disorder that occurs due to trisomy on chromosome 21. It is known to relate to the amyloid-beta (A4) precursor protein (APP) gene and amyloid plaques, affecting developmental processes and resulting in early dementia, signifying a relation to Alzheimer's disease (AD). AD in individuals with DS affects many aspects include memory function, social and cognitive behavior. There is also a high likelihood for individuals with DS to have an AD at an early age, adding more challenges to the patients and the caregivers. Triplication of the gene in DS and an extra copy of APP in familial AD patients are responsible for the genetic link between these two diseases.